Effects of different shoe-lacing patterns on the biomechanics of running shoes - Hagen, M.; Hennig, E. M. (Journal of Sports Sciences, 2009)
In the present study, we examined the influence of shoe lacing on foot biomechanics in running. Twenty experienced rearfoot runners ran in six different lacing conditions across a force platform at a speed of 3.3 m · s-1. Foot pronation during contact, tibial acceleration, and plantar pressure distribution of the right leg were recorded. The test conditions differed in the number of laced eyelets (1, 2, 3, 6 or 7) and in lacing tightness (weak, regular or strong). The results show reduced loading rates (P < 0.05) and pronation velocities (P < 0.01) in the tightest and highest lacing conditions. The lowest peak pressures under the heel and lateral midfoot (P < 0.01) were observed in the high (seven-eyelet) lacing pattern. Regular six-eyelet cross-lacing resulted in higher loading rates (P < 0.05) and higher peak heel pressures (P < 0.01) than seven-eyelet lacing, without any significant differences in perceived comfort. The low lace shoe conditions resulted in lower impacts (P < 0.01) and lower peak pressures under metatarsal heads III and V (P < 0.01), which is probably induced by the foot sliding within the shoe. A firm foot-to-shoe coupling with higher lacing leads to a more effective use of running shoe features and is likely to reduce the risk of lower limb injury.